Klang valley transit traveller - Zakiah, Apandi (2019)
Nowadays, public transport has been used as the main transport for Malaysians. For example, the KTM Komuter. The KTM Komuter has been used widely in this era. The problems are when the user want to use the KTM Komuter they needs to purchase the ticket first before they can go to their destination. It will take time for the user to purchase the ticket due to the numbers of people who used the KTM as their main transport. Besides, the chances to lose their ticket are higher. For the user who used the KTM Komuter for the first time, they will take time to know the route of their destination. Furthermore, they need to ask or find someone who knows the ticket price for their destination. The resolution for the problems is the Klang Valley Transit Traveller will be developed. Klang Valley Transit Traveller is a web system that allow user to know the route map of KTM Komuter, the ticket price for each station and the availability of the quantity ticket for each station. This system is focus on user who used the KTM Komuter as their main public transport. The objectives of this system are to help user to know and explore the KTM Komuter route map. Besides, to ensure user to know the route of the KTM Komuter station, the ticket price of the each KTM station and the availability of the quantity ticket for each KTM station.